FIFTH COLOMBIAN CONFERENCE OF PHARMACEUTICAL CARE: "HARNESSING THE DIGITAL REVOLUTION TO IMPROVE THE PROCESSES AND RESULTS OF PHARMACEUTICAL CARE" - COLOMBIAN CONFERENCE OF PHARMACEUTICAL CARE, FIFTH (Vitae, 2019)
.